Comparative analysis of racing performance following surgical correction of epiglottic entrapment in standardbreds and thoroughbreds - Norton, Alannah M.; Rosanowski, Sarah M.; O’Brien, Tom (Frontiers in Veterinary Science, 2024)
IntroductionEpiglottic entrapment (EE) is a common cause of poor performance in racing standardbreds (STBs) and thoroughbreds (TBs). There is limited information published on the condition in STB racehorses and limited information on factors associated with return to racing available for either breed.MethodsThis study investigated and compared the pre surgical findings, post-surgical complications and racing performance in STBs and TBs undergoing surgery for correction of EE. Associations between signalment and pre-surgical findings, and the presence of complications and racing post-surgery were compared using logistic regression analyses. Racing performance following surgery was compared to maternal siblings using conditional logistic regression.ResultsThere were 82 cases where epiglottic entrapment surgery was performed at least once: 33 STB cases and 49 TB cases. In total, 74% of cases raced following surgery. Cases with severe inflammation post-surgery (p < 0.001), airway complications (p < 0.001) or an epiglottic re-entrapment (p < 0.01) were at a lower odds of racing post-surgery. TB cases were 5.5 times (95% Confidence interval 1.61 to 18.73) more likely to race than their maternal siblings (p < 0.01). TB cases took 79% longer to return to racing compared to STB cases (p < 0.001). Horses that had raced prior to surgery were 4.1 times more likely to race after surgery than those that had not (95% CI 1.01–16.67).ConclusionHorses with post operative complications were at a lower odds of racing post surgery. In the current study, TBs with EE are more likely to race compared to their maternal half siblings however take longer to return to racing compared to STBs.